Oriented regular representations of out-valency two for finite simple groups - Verret, Gabriel (Ars mathematica contemporanea, 2022)
In this paper, we show that every finite simple group of order at least 5 admits an oriented regular representation of out-valency 2.
Keywords: DRR; finite simple group; končna enostavna grupa; ORR